Development of Reflective Thinking through Distance Teacher Education Programs at AIOU Pakistan - Buzdar, Muhammad Ayub; Ali, Akhtar (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
The current study aims to investigate the possibilities of developing reflective thinking among learners through distance education programs. The case of Allama Iqbal Open University (AIOU) Islamabad, Pakistan is examined to achieve this task. The study is based on Mezirow’s theory of reflective thinking, which divides thinking in four categories. The Questionnaire of Reflective Thinking (QRT) developed by Kember et al. (2000) based on Mezirow (1991) was administered to 450 AIOU students. The thinking and learning practices of students governed by their habitual actions, understanding, reflection, and critical reflection are statistically examined to meet the research objectives. Findings reveal that AIOU teacher education programs have a stronger tendency to promote understanding and reflective thinking among learners. The need to integrate content for developing critical reflection among learners is highlighted. The study also discovers the significant impacts of students’ job status and previous qualifications on their thinking patterns.